Effects of Intracoronary Pro-urokinase or Tirofiban on Coronary Flow During Primary Percutaneous Coronary Intervention for Acute Myocardial Infarction: A Multi-Center, Placebo-Controlled, Single-Blind, Randomized Clinical Trial - Huang, Dong; Qian, Juying; Liu, Zongjun; Xu, Yawei; Zhao, Xianxian; Qiao, Zengyong; Fang, Weiyi; Jiang, Li; Hu, Wei; Shen, Chengxing; Liang, Chun; Zhang, Qi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: To determine whether intracoronary pro-urokinase or tirofiban improves myocardial reperfusion during primary percutaneous coronary intervention (PCI) for acute ST-segment elevation myocardial infarction (STEMI). Methods: The study included patients with acute STEMI presenting within 12 hours of symptoms at 11 hospitals in China between November 2015 and July 2017. Patients were randomized to receive selective intracoronary infusion of recombinant pro-urokinase (20 mg), tirofiban (10 µg/kg) or saline (20 mL) proximal to the infarct-related lesion over a 3-minute period before stent implantation during primary PCI. The primary outcome was final corrected thrombolysis in myocardial infarction (TIMI) frame count (CTFC) after PCI. Results: This study included 345 patients. Initial angiography identified a high-grade thrombus (TIMI 4–5) in 80% of patients. Final CTFC after PCI was significantly lower in the pro-urokinase (P < 0.001) and tirofiban (P < 0.001) groups than in the saline group and similar between the pro-urokinase and tirofiban groups (P >0.05). The pro-urokinase (P = 0.008) and tirofiban groups (P = 0.022) had more complete ST-segment resolution at 2 hours and lower peak creatine kinase-MB levels after PCI than the saline group (P = 0.006 and P = 0.023). The 30-day incidence of major adverse cardiac events was 4.5% in the pro-urokinase group, 3.4% in the tirofiban group and 2.6% in the saline group. The incidence of in-hospital TIMI major bleeding events was low and comparable between groups. Conclusions: Adjunctive intracoronary pro-urokinase or tirofiban given before stent implantation during primary PCI improves myocardial reperfusion without increasing the incidence of major bleeding events.